PENGEMBANGAN BAHAN AJAR HANDOUT BIOLOGI BERBASIS PENGEMBANGAN BAHAN AJAR HANDOUT BIOLOGI BERBASIS PENGEMBANGAN BAHAN AJAR HANDOUT BIOLOGI BERBASIS PENGEMBANGAN BAHAN AJAR HANDOUT BIOLOGI BERBASIS PENGEMBANGAN BAHAN AJAR HANDOUT BIOLOGI BERBASIS PENGEMBANG - Purwati, Dwi - (STKIP PGRI Sumbar, 2014)
In Biologi subject is needed the material with picture that support teaching materials, because of that the teacher is required to develop teaching materials with variations.There is one way to develop teaching materials by making an insteuctional materials like handout.Based on the result of writer observationÂ to SMPN 20Tebo regency Jambi showed that the process of Biology learning system of human excretion in materials, the teacher were not using handout yes as intructional materials. The students only used support books from the school and worksheets, but it has some shortcomings, such as the number of books limited and it was only duringthe time of study,the pictures was presented in the book is less complete,the colour did not resemble with the original colour is only black and white colour and written information was not clear. The purpose of this research is to produce handout biology materials based on colour of the pictures with map concept at the material human excretion for junior high school that valid and practical. This research is development research with using 4-D models that consists from define step, design, develop and disseminate. However, disseminate step was not done.Define step consists of a frontÂ end analysis,analysis of student and task analysis materials in junior high school,and at develop step was done validity test by valodator that consists at 2 lecturesÂ and 2 teachers biologi SMPN 20 Tebo Jambi.Practical test by 2 teachers biology and 15 students class IX SMPN 20 Tebo Jambi.The result of data analysis showed that handout based on the picture in the system of human excretion material was very valid and very practical, with validity value 88,96%, and with practicalitas value 92,09%, this thing showed that handout based on the pictures in the system of human excretion materials that was produced very valid and very practical.